Greenhouse gas cycling by the plastisphere: The sleeper issue of plastic pollution. (May 2020) - Cornejo-D'Ottone, Marcela; Molina, Verónica; Pavez, Javiera; Silva, Nelson
Abstract: Plastic is an allochthonous material to marine ecosystems but is rapidly colonized by marine microbial communities, with an as yet unclear contribution to biogeochemical cycles. In this study, we investigated the influence of an active microbial community grown on microplastic particles (the plastisphere) on CO2 and N2 O recycling and its potential role in greenhouse gas inventories and air-sea exchange. Microplastics were collected during two cruises (Cimar 21 and FIP Montes Submarinos) from the surface layer (5 m depth) from several contrasting trophic regions of the South Pacific Ocean, i.e., from a transition zone off the eutrophic coastal upwelling of Chile, to a mesotrophic transition area of oceanic seamounts and, finally, to an oligotrophic zone in the South Pacific Subtropical Gyre. . Experiments were carried out onboard to evaluate CO2 and N2 O production/consumption by the plastisphere. The active microbial community and its specific quantification were determined for Cimar 21 using iTag 16 S rRNA. The experiments showed that the plastisphere generally contributed to CO2 and N2 O production/consumption, with rates ranging from −20.5 (consumption) to +4.5 (production) μmol/m 2 /d. The seamounts and the transition zone presented the highest production/consumption rates. The experiments performed in the two seamount stations showed that production and consumption of CO2 were related to the environmental nutrient concentration. Both stations presented N2 O consumption that was associated with the high nitrogen deficit of the subantarctic water mass. The transition zone presented CO2 and N2 O production in a plastisphere dominated by heterotrophic communities. The plastisphere in oligotrophic waters was diverse and active. The experiments, however, presented low or no production of greenhouse gases. Our results show a contribution of CO2 and N2 O to the global gas surface inventories and air-sea exchange is lower than 1% of the global sources. These results highlight different critical impacts of plastic pollution on the environment that have, until now, not been considered. Highlights: Plastisphere of the eastern South Pacific recycles greenhouse gases. The highest activity occurred close to the productive coastal region. The lowest activity occurred in the subtropical gyre of the South Pacific. GHG cycling seems to be driven by surface biogeochemical conditions. The plastisphere CO2 and N2O contribution is less than 1% of the ocean contribution.